2013
DOI: 10.21608/jvmr.2013.77693
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Enteric Parasites of Zoo Animals and Zookeepers in Beni-Suef Governorate, Egypt

Abstract: In this study, the enteric parasites of zoo animals and zookeepers in Beni-Suef governorate, Egypt were investigated. Fecal samples from thirteen animal species were examined by floatation and formol ether sedimentation techniques. Zoo animals were classified into non-human primates, carnivores and herbivorous animals. The examination of non-human primates revealed the presence of Trichuris trichura eggs, Giardia intestinals and Entamoeba histolytica cysts. In carnivores, Toxoascaris leonina eggs and Isospora … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Among carnivorous animals, we only found positive samples in some species of the order Carnivora and in the giant anteater (order Pilosa) (Tables 3 and 5). In species of the order Carnivora, the vast majority of findings occurred only once or twice over the 10 years of sampling, and except for four positive samples for Capillaria, the parasites now found do not correspond to those generally detected in other studies, which report ascarids, whipworms, and strongyles [13,25,31,34,44,60,62].…”
Section: Mammalian Hostscontrasting
confidence: 80%
See 2 more Smart Citations
“…Among carnivorous animals, we only found positive samples in some species of the order Carnivora and in the giant anteater (order Pilosa) (Tables 3 and 5). In species of the order Carnivora, the vast majority of findings occurred only once or twice over the 10 years of sampling, and except for four positive samples for Capillaria, the parasites now found do not correspond to those generally detected in other studies, which report ascarids, whipworms, and strongyles [13,25,31,34,44,60,62].…”
Section: Mammalian Hostscontrasting
confidence: 80%
“…In a previous molecular-based investigation [ 15 ], there was no evidence of transmission between these parasites and the personnel at ZooAquarium and Faunia; however, zoonotic transmission was detected for Cryptosporidium hominis Morgan-Ryan et al 2002 and Blastocystis (Alexeieff 1911) spp. In some studies conducted in other zoos, potential transmission of parasites to zoo personnel was also suggested [ 11 , 12 , 13 , 14 , 131 , 132 ]. The risk of transmission to visitors is low, as contact with animals is generally limited or nonexistent; however, zookeepers and veterinarians are exposed during handling and cleaning operations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spread of gastrointestinal parasites among zoo animals by zoo keepers were reported by several authors [16] [26] [35]. Arafa et al [45] reported that unhygienic zoo keepers can potentially transmit parasites between the animals especially when the life cycle is direct.…”
Section: Dashe a Berhanumentioning
confidence: 99%